Human beta-defensin 1, 2 and 3 production by amniotic epithelial cells with respect to human papillomavirus (HPV) infection, HPV oncogenic potential and the mode of delivery. (August 2016) - Szukiewicz, Dariusz; Alkhalayla, Habib; Pyzlak, Michal; Watroba, Mateusz; Szewczyk, Grzegorz; Wejman, Jaroslaw
Abstract: Background: Human beta-defensins (HBD) produced by human amniotic epithelial cells (HAEC) co-create an innate antiviral immune response in the materno-placento-fetal unit. Oncogenic potential of HPV may reflect its ability to avoid immune recognition. In this study we assessed the risk of HAEC infection with human papillomavirus (HPV) in relation to the type of labor and the impact of the oncogenic potential of HPV on HBD production in HAEC. Methods: A comparative analysis [HPV(+) vs. HPV(−)HAEC] of the production of HBD were performed. HAEC were isolated from placentas of 116 HPV(+) and 36 HPV(−) parturients (groups I and II, respectively) using trypsin-based method. The cases of premature rupture of membranes (PROM), natural labors (NL) and cesarean sections (CS) were analysed in respective subgroups. High-risk (HR-HPV) and low-risk (LR-HPV) genotypes of HPV in cervical smears and HAEC were identified using the Roche Linear Array ® HPV Genotyping Test. HBD-1, -2, -3 concentrations in the HAEC culture supernatant were assessed using ELISA. Results: The highest percentage (42.1%) of HPV transmission to HAEC occurred in PROM, an intermediate value was observed after NL (38.5%), and the lowest (25.6%) after CS. The mean concentrations of HBD-2 and HBD-3 in group I were up to 3.1- and 2.8-fold higher (p < 0.05), respectively. The mean concentration of HBD-2 was higher (p < 0.05) in LR-HPV infection compared with HR-HPV. Conclusions: The course of labor and the mode of delivery influence the risk of HPV transmission to the HAEC. HPV infection upregulates HBD-2 and HBD-3 production in HAEC. Smaller increases in HBD-2 level after HR-HPV infection as compared to LR-HPV may affect cancerogenesis. Therapeutic potential of HBD-2 for HR-HPV infection should be assessed in future studies. Highlights: β-Defensins (HBD) are involved in immune response to HPV infection in pregnancy. Risk of HPV DNA transmission to amniotic membrane depends on delivery mode. Down-regulated expression of HBD-2 may affect high-risk HPV-related cancerogenesis. Therapeutic potential of HBD-2 for high-risk HPV infection should be considered.